Safe Treatment of Surface Coalfield Fires Above Shallow-Buried Goaf in Steeply Dipping Coal Seams - Pihong Zhang; Ruchang Chen; Guoqing Zhu; Dezhi Yang; Xin Li; Wei Jiang; Hao Liu; Zhiyi Zhang (Fire)
Xinjiang is a region of China that suffers severe energy resource loss and air pollution resulting from long-term coalfield fires in near-surface inclined coal seams. Beneath these fire areas, abandoned mined-out goaf is common. Accidents easily occur during the treatment of such fire areas owing to the instability of strata overlying the goaf. Here, we carried out non-destructive exploration of the goaf below a fire area using the airborne transient electromagnetic method, accurately identifying the locations and sizes of 21 goaf areas. We then established a stratigraphic model using the thermal-solid coupling function in UDEC software. Our simulations showed that under the combined action of high temperature generated by coal combustion and high pressure generated by fire-fighting machinery, the maximum displacement and vertical stress in strata overlying the goaf were 1.42 m and 36 MPa, respectively. Such large displacement and stress values inevitably lead to the destabilization of overlying strata via turning, sliding, and tipping, seriously threatening the safety of mining personnel and machinery. In the field, the rock layer above the goaf was first accurately blasted, and then fire extinguishing was carried out after the overlying rock had collapsed and compacted.